Colletotrichum aotearoa B. Weir & P.R. Johnst causing leaf anthracnose in Lithocarpus litseifolius in China - Yuling Wang; Chang Liu; Guolin Cai; Ning Shu; Ziqiang Luo; Zixuan Qiu; Wuping Yan (Crop Protection, 2026)

Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Bifunctional starch nanoparticles for achieving recyclable interfacial biocatalysis within a narrow pH range - Liang Qi; Yujing Zhou; Yuling Pan; Cong Zhang; Xiaojuan Xu; Xin Cai (Carbohydrate Polymers, 2026)

Clinical study on the interaction between iron metabolism and neuroinflammation and iron deposition in the substantia nigra of Parkinson’s disease - Yani Yao; Jiayi Li; Jiaoyang Yan; Qian Cai; Yuling Wang; Huan Xia; Tingting Feng; Peishan Li; Xinling Yang (Brain Imaging and Behavior, 2026)

Nanomaterials in the food industry: applications and potential health risks - Wenrui Li; Suyu Lin; Luyao Zhang; Jiachen Yu; Yuling Cai; Di Wu; Yongning Wu; Guoliang Li (Food Chemistry, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Human Cortical Organoids with a Novel SCN2A Variant Exhibit Hyperexcitability and Differential Responses to Anti-Seizure Compounds - Yuling Yang; Yang Cai; Shuyang Wang; Xiaoling Wu; Zhicheng Shao; Xin Wang; Jing Ding (Neuroscience Bulletin, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

Mineral-element-chelating activity of food-derived peptides: influencing factors and enhancement strategies - Chaonan Cai; Yuting Liu; Yuling Xu; Juntao Zhang; Benmei Wei; Chengzhi Xu; Haibo Wang (Critical Reviews in Food Science and Nutrition, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Superoxide anion radicals mediated degradation of tetrachloropicolinic acid in biochars-Fe P@Fe-FexC/O2 system with excellent reactivity durability - Hongyun Niu; Shaojie Shi; Siyu Zhu; Yuling He; Qiwen An; Hao Ding; Xuwenqi Zhang; Dongbin Wei; Yali Shi; Yaqi Cai (Water Research, 2025)

Evaluation of the freshness (TVB-N) of pork patty during storage based on PLS-DA, SVM and BP-ANN models - Hui Lu; Aiying Song; Ming Li; Xianqi Yao; Yuling Cai; Longlong Dong; Dacheng Kang; Yunguo Liu (Food Control, 2025)

Exploration on antifreeze potential of thawed drip enzymatic hydrolysates on myofibrillar proteins in pork patties during freeze-thaw cycles - Xiaoyu Han; Yang Li; Ying Wang; Jinpeng Wang; Wendi Teng; Longlong Dong; Yuling Cai; Jinxuan Cao; Yuemei Zhang (Food Chemistry, 2025)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Photocatalytic removal of ammonia nitrogen from water: investigations and challenges for enhanced activity - Huining Zhang; Yang Cao; Shaofeng Wang; Yuling Tang; Lihong Tian; Wenrui Cai; Zhiqiang Wei; Zhiguo Wu; Ying Zhu; Qi Guo (Environmental Science and Pollution Research, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Persulfate oxidation of norfloxacin by cobalt doped water hyacinth biochar composite: The key role of cobalt and singlet oxygen - Yunqiang Yi; Yue Fu; Yu Wang; Yuling Cai; Yifeng Liu; Zhimin Xu; Zenghui Diao (Journal of Water Process Engineering, 2024)

Review: Specific storage in aquitards - Yinong Cai; Yuling Yin; Xingxing Kuang; Yinlei Hao; Junguo Liu; Chunmiao Zheng (Hydrogeology Journal, 2023)

Larvicidal, acetylcholinesterase inhibitory activities of four essential oils and their constituents against Aedes albopictus, and nanoemulsion preparation - Yuling Li; Weifeng Wu; Rongchao Jian; Xiaofei Ren; Xiaole Chen; Weiqian David Hong; Min Wu; Jinglin Cai; Canyao Lao; Ximing Xu; Zhaojun Sheng (Journal of Pest Science, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

Activated abscisic acid pathway and C4 pathway, inhibited cell cycle progression, responses of Ulva prolifera to short term high temperature elucidated by multi-omics - Hui Zhao; Xuanhong Liu; Ting Jiang; Chuner Cai; Kai Gu; Yuling Liu; Peimin He (Marine Environmental Research, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Physiological and biochemical responses and microscopic structure changes of Populus tomentosa Carr seedlings to 4-BDE exposure - Man Cai; Yuling Li; Yanling Li; Kejiu Du (Environmental Science and Pollution Research, 2015)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)